Impacto de redes de distribuição com massiva conexão de geradores fotovoltaicos na estabilidade de tensão de longo-prazo em sistemas de potência - BARATA, Heitor Alves (Universidade Federal do Pará, 2017)
This dissertation aims to show the impact of distributed photovoltaic generators connected to distribution networks on long term voltage stability using full time simulation. The effect of different penetration levels of photovoltaic generation is investigated. Different distribution network models considering distributed generation (DG) connections is also investigated: 1) Load and DG represented by ZIP model and negative active power loads, respectively, connected to the substation bus; 2) Load and DG represented by ZIP model and dynamic equivalent, respectively, connected to the substation bus; 3) Load and GD represented by ZIP model and dynamic model, respectively, distributed along a MV distribution network. Equipments such as On-Load Tap Changer (OLTC) transformers, Overexcitation Limiter (OEL), static loads and step voltage regulators are taken into account in the analyzes, since they significantly affect the long-term voltage stability. The investigations were conducted using both the power flow software ANAREDE and transient stability simulator ANATEM, developed by the Electrical Energy Research Center (CEPEL). For the purpose of power flow studies, photovoltaic generators are modeled as PQ buses with Q=0. The modelling of photovoltaic generators for dynamic studies is based on WECC (Western Electricity Coordinating Council) model, wich was inserted into file User Defined Controller (CDU) from ANATEM. The undervoltage protection of photovoltaic generator is also considered. The case studies were performed on a combined transmission and distribution model.